2017
DOI: 10.1186/s12885-017-3108-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary stop of the TOPical Imiquimod treatment of high-grade Cervical intraepithelial neoplasia (TOPIC) trial

Abstract: The “TOPical Imiquimod treatment of high-grade Cervical intraepithelial neoplasia” (TOPIC) trial was stopped preliminary, due to lagging inclusions. This study aimed to evaluate the treatment efficacy and clinical applicability of imiquimod 5% cream in high-grade cervical intraepithelial neoplasia (CIN). The lagging inclusions were mainly due to a strong patient preference for either of the two treatment modalities. This prompted us to initiate a new study on the same subject, with a non-randomized, open-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…Because of local and systemic side effects Imiquimod is inappropriate for the treatment of CIN1 [35]. A new trial with Imiquimod for CIN2 + had to be stopped due to the lack of appropriate patients to be included in the study, because many preferred either the Large Loop Excision of the Transformation Zone (LLETZ) procedure or the Imiquimod treatment [36].…”
Section: Discussionmentioning
confidence: 99%
“…Because of local and systemic side effects Imiquimod is inappropriate for the treatment of CIN1 [35]. A new trial with Imiquimod for CIN2 + had to be stopped due to the lack of appropriate patients to be included in the study, because many preferred either the Large Loop Excision of the Transformation Zone (LLETZ) procedure or the Imiquimod treatment [36].…”
Section: Discussionmentioning
confidence: 99%
“…Imiquimod is a TLR7 agonist with proven antitumor activity as a topical treatment for skin cancer. At the moment, it is approved by US FDA and many phase 2 clinical trials show its safety and efficacy in other types of cancer, such as carcinoma in situ bladder cancer [112], cervical intraepithelial neoplasia [113], or breast cancer cutaneous metastases [114].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the effect of imiquimod in CIN and showed the adverse effects to be well-tolerated [ 4 , 5 ]. Currently, a non-randomised study comparing the effectiveness of imiquimod treatment with large loop excision of the transformation zone (LLETZ) is being performed in the Netherlands (TOPIC-3) [ 6 ]. The patients were instructed to administer one sachet containing 12,5 mg of 5% imiquimod with a vaginal applicator three times weekly intravaginally.…”
Section: Introductionmentioning
confidence: 99%